Molecular Diagnosis of Human Rhinovirus Infections: Comparison with Virus Isolation - Hyypiä, Timo (American Society for Microbiology, 1998)
To compare the sensitivity and specificity of RT-PCR with that of virus isolation in the detection of human rhinoviruses, we tested nasopharyngeal aspirates from 200 patients on the 1st and 7th days after the onset of the common cold. An assay utilizing a short amplicon in the conserved 5′ noncoding region was found highly sensitive. Of 192 positive samples altogether, 65 were found positive by RT-PCR only, 6 were positive by isolation exclusively, and 121 gave positive results in both tests.